HYDROGEOCHEMISTRY FOR THE ASSESSMENT OF GROUNDWATER QUALITY OF SPRINGS ON ANDROS: AN ISLAND OF THE CYCLADES COMPLEX, GREECE - Filippidis, F.; Stamatis, G.; Mantaloufa, I. (Bulletin of the Geological Society of Greece, 2016)
The paper presents the results of the physicochemical parameters of the springs of Andros which were studied to evaluate the chemistry of the major ions and solute acquisition processes, which control the chemical composition and the suitability of the quality of water for drinking use. Forty two samples were taken for physicochemical analysis almost at the end of the summer period, in September 2014. The Piper plot was used for the hydrogeochemical classification of groundwater which also indicated that the majority of groundwater samples belong to the Ca-Na-HCO3-Cl type. According to the Durov plot the majority of samples, can be positioned in field 2 in which a process of cation exchange is in progress. Also, the HCO3 /(HCO3 +SO4) ratio indicates a weathering process from carbonic acid. In general, the majority of samples can be characterized as potable.